Exploring the long-run and short-run elasticities between FDI inflow and its determinants in Jordan - Bekhet H.A.; Al-Smadi R.W. (Inderscience Publishers, 2023)
This paper investigates the long-run and short-run elasticities among Greenfield investment inflows, gross domestic product, energy consumption, economic openness, gross fixed capital formation, labour and financial development in Jordan. Annual time series data for the 1979-2012 periods and the ARDL bounding test are used. The results identify long-run and short-run elasticities in foreign direct investment (FDI) and its determinants. In general, Jordanian policy makers concentrate their efforts to attract more FDI by enhancing economic indicators and liberalising the financial market. This is because more FDI in the Jordanian economy is expected to lead to a decrease in economic obstacles (e.g., lower unemployment rate, increased level of technological and managerial skills and increased size of capital). Copyright 2017 Inderscience Enterprises Ltd.